Inspired by my Best Friend

Geometry Level 4

cot 1 2 + cot 1 8 + cot 1 18 + = ? \Large \cot ^{-1} 2 + \cot ^{-1} 8 + \cot ^{-1} 18 + \ldots = \ ?

Give your answer to 3 decimal places in radians.

Clarification : 2 , 8 , 18 , 2,8,18,\ldots are twice a perfect square.


This is not my original problem.


The answer is 0.78539816339.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Let S = cot 1 2 + cot 1 8 + cot 1 18 + S=\cot^{-1} 2+\cot^{-1} 8+\cot^{-1} 18+\cdots , then S = n = 1 cot 1 ( 2 n 2 ) S=\displaystyle \sum_{n=1}^{\infty} \cot^{-1} (2n^2) or S = n = 1 tan 1 ( 1 2 n 2 ) S=\displaystyle \sum_{n=1}^{\infty} \tan^{-1}\left(\dfrac{1}{2n^2}\right) .

Then notice that 1 2 n 2 = 2 4 n 2 = ( 2 n + 1 ) ( 2 n 1 ) 1 + ( 2 n + 1 ) ( 2 n 1 ) \dfrac{1}{2n^2}=\dfrac{2}{4n^2}=\dfrac{(2n+1)-(2n-1)}{1+(2n+1)(2n-1)} . With this we can make this sum telescope:

S = n = 1 tan 1 ( ( 2 n + 1 ) ( 2 n 1 ) 1 + ( 2 n + 1 ) ( 2 n 1 ) ) S=\displaystyle \sum_{n=1}^{\infty} \tan^{-1}\left(\dfrac{(2n+1)-(2n-1)}{1+(2n+1)(2n-1)}\right)

Finally, we apply the identity tan 1 ( a ) tan 1 ( b ) = tan 1 ( a b 1 + a b ) \tan^{-1}(a)-\tan^{-1}(b)=\tan^{-1}\left(\dfrac{a-b}{1+ab}\right)

S = n = 1 ( tan 1 ( 2 n + 1 ) tan 1 ( 2 n 1 ) ) S=\displaystyle \sum_{n=1}^{\infty}(\tan^{-1}(2n+1)-\tan^{-1}(2n-1))

Then, we are only left with this two terms:

S = tan 1 ( ) tan 1 ( 1 ) = π 2 π 4 = π 4 S=\tan^{-1}(\infty)-\tan^{-1}(1)=\dfrac{\pi}{2}-\dfrac{\pi}{4}=\boxed{\dfrac{\pi}{4}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...